The Ontological Status of Christian Eschatology - KUI, Renlian; AN, Ximeng (Journal of Research for Christianity in China (JRCC), 2023)
Chapter  V , The  Question  of an Eschatological  Ontology, in The  Logic   of  Promise in Moltmann's  Theology, Christopher  Morse, Philadelphia Fortress  Press, 1979.